Japanese mythology - Piggott, Juliet (New York, N.Y. : P. Bedrick Books : Distributed in the USA by Harper & Row, 1983)
Discusses the mythology of Japan, its origins in Shintoism and Buddhism, and the gods, spirits, men, and animals that appear in the many legends and stories.
Includes index.
Bibliography: p. 142.
Keywords: Mythology, Japanese